Poza metaforą – autyzm jako impas hermeneutyczny w powieści postkolonialnej - Kołodziejczyk, Dorota (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
A lot of postcolonial novels feature characters with disordered communication, unable to express their will, existing outside of language. These most often unnamed traces of autism and/or intellectual disability become in fictional narrative an element disturbing the expected outcome of postcolonial vindications, out of which the most important is regaining by a marginalized character the sense of subjectivity, realized as a possibility to tell one’s own story. Basing on Ato Quayson’s concept of “aesthetic nervousness”, the article traces how literary and cultural representations of disability introduce into a text affective-cognitive mechanisms which reveal, as Ato Quayson says, “heremeneutic impasse” caused by a confrontation of the norm with disability. This blocked path of text interpretation poses the radical example of untranslatability which will not be abated or compensated by the effort to substitute lack represented by the autistic subject (lack of speech, communication, subjectivity – in general – lack of participation in the universe of interlocution, as Seyla Benhabib calls it). Hermeneutic impasse is, then, inscribed in the very narrative structure featuring an autistic character. On the basis of J. M. Coetzee’s novels, the article analyses this impasse as resistance that untranslatability poses against the attempts to understand, that is, represent, such a subject. These attempts, ethical as to their purpose, end up, however, in containment.